A systematic review of Astragalus plants in the septentrional Algerian Sahara - Tedjani, Aicha; Azzi, Manel; Righi, Nouhad Amina; Chemsa, Ahmed Elkhalifa; Mouane, Aicha; Boual, Zakaria; Laib, Ibtissam; Atoki, Ayomide Victor; Messaoudi, Mohammed (Frontiers in Nutrition, 2025)
BackgroundThe flora of the septentrional Algerian Sahara stands out for its remarkable resilience in the face of drought and salinity, offering a valuable resource with diverse applications in food, aromatics, and medicine. Among these resilient plants, the Astragalus genus emerges as a prominent member of the Fabaceae family.ObjectiveThis systematic review delves into the description, distribution, utilization, systematic classification, and chemical composition of key Astragalus species in the septentrional Algerian Sahara, with a particular emphasis on their medicinal applications.MethodsWe will conduct a comprehensive search across PubMed, Scopus, ScienceDirect, and Google Scholar from October 1, 2018, to June 2024, without language restrictions. This study will follow a systematic review approach, incorporating narrative description and realist synthesis. Our study addresses gaps in knowledge concerning several under-documented Astragalus species, including A. armatus, A. cruciatus, A. gombo, and A. gyzensis. Widely distributed across the septentrional Algerian Sahara, these species are distinguished by their unique biochemical profiles, comprising saponins, phenolic compounds, and polysaccharides, which confer upon them a range of medicinal and therapeutic properties.ConclusionThis research aims to fill the knowledge void surrounding lesser-known Astragalus species, providing comprehensive insights to the scientific community. However, it is imperative to recognize the necessity for further critical assessment and empirical validation to confirm and elaborate on these findings. Such endeavors are pivotal for fully harnessing the potential of these extraordinary plants for human benefit.